MAULANA AZAD’S RELIGIOUS PSYCHE AND PHILOSOPHY OF WAHDAT-E ADYAN AND ITS RELEVANCE - Hussain, Muzaffar (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
With More than 1700 tafaseer of Al-Quran (commentaries of Al-Quran) till recently leading to more than 187 Islamic sects so far, only two tafaseer of Al-Quran are unique and explain the Quranic Epistemology in altogether different luminosities. The one is by Sir Syed Ahmad Khan and the other by Maulana Abul Kalam Azad. Like Sir Syed Ahamd Khan, Maulana Azad also rebelled and thoroughly dissented against the continuing tradition of ‘orthodox version’ of tafseer. He provided the basic foundations for the future generations to correctly understand Al-Quran, by putting away the fairy notions of Jannah, houries, jinn and other such metaphysical unexplained supernatural phenomena. and everything harmonious rather he deduced from Quran the very hard facts that Quran exhorts its believer to “to remain constantly in action and work hard…so that Allah could elevate the qaum of believers to the highest pedestal here in this world and hereafter” different notion from the stock of great Tafseer writers, but his Tafseer could transfigure in quite dissimilar parameters as against those who toed the line of earlier Tafseer writers.